Reseña: Cappuccio, M.; T. Froese, T, eds. 2014. Enactive Cognition at the Edge of Sense-making. Making Sense of Non-sense. Basingstoke, Hampshire: Palgrave Macmillan. New Directions in Philosophy and Cognitive Science, 317 pp. - Vizcaya, Susana Ramírez (Open Insight, 2018)
Reseña de Cappuccio, M.; T. Froese, T, eds. 2014. Enactive Cognition at the Edge of Sense-making. Making Sense of Non-sense. Basingstoke, Hampshire: Palgrave Macmillan. New Directions in Philosophy and Cognitive Science, 317 pp.